Tom Newbound and his sister, Mrs Montgomery sing folk songs in the Norm O'Connor folklore collection - Newbound, Tom, -1960.; Montgomery, Mrs.; O'Connor, Norman; Folk Lore Society of Victoria (1959)
Folkloric recording.
16. No sir, no sir -- 17. No sir, no sir -- No sir, no sir.
A collection of recordings and related material collected during the 1950s and 1960s by Norm O'Connor Pat O'Connor and others for the Folk Lore society of Victoria.
Digital master available
Transcript unavailable.
Keywords: Folk songs, English -- Australia